2022
DOI: 10.1038/s41598-022-10555-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-angle quantum approximate optimization algorithm

Abstract: The quantum approximate optimization algorithm (QAOA) generates an approximate solution to combinatorial optimization problems using a variational ansatz circuit defined by parameterized layers of quantum evolution. In theory, the approximation improves with increasing ansatz depth but gate noise and circuit complexity undermine performance in practice. Here, we investigate a multi-angle ansatz for QAOA that reduces circuit depth and improves the approximation ratio by increasing the number of classical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…There are several adaptions to the simple p-level QAOA method described in the main text in Sec. II A [38,42,[66][67][68][69][70][71][72][73]. For instance, the Quantum Alternation Operator Ansatz [38] (QAOA+) provides a more expressive variational state by modifying the definitions of U x (β) and U p (γ).…”
Section: Appendix E: Parity Qaoa+mentioning
confidence: 99%
“…There are several adaptions to the simple p-level QAOA method described in the main text in Sec. II A [38,42,[66][67][68][69][70][71][72][73]. For instance, the Quantum Alternation Operator Ansatz [38] (QAOA+) provides a more expressive variational state by modifying the definitions of U x (β) and U p (γ).…”
Section: Appendix E: Parity Qaoa+mentioning
confidence: 99%
“…Prior work, investigating the application of the QAOA to MaxCut problems, has shown that allowing the partial mixers to be uniquely parameterized in this way can lead to increased approximation ratio and reduced circuit depth at the expense of an increased number of variational parameters [14]. However, the QLS ansatz differs from that considered in [14] because the partial mixers do not commute with one another. This allows us to randomize over different permutations of the partial mixers to escape local minima.…”
Section: Neighborhood Ansatz Constructionmentioning
confidence: 99%
“…We evaluate the application fidelity of QAOA circuits using Approximation Ratio Gap (ARG) from prior works [8,41,60], as defined in Equation ( 4).…”
Section: Figure Of Meritmentioning
confidence: 99%